Pengaruh Penyederhana Amalan Pembangunan Sumber Manusia Terhadap Hubungan Amalan Operasi Perkhidmatan dan Prestasi Pihak Berkuasa Tempatan di Semenanjung Malaysia - Mohd Nazri, Zakaria (2011)
An efficient service delivery system is a priority of the government in general and local authorities in particular in line with the wishes of the community. However, studies in this field are still lacking, particularly in the public sector. Therefore, this study focuses on the level of service operations practices adopted by local authorities and its relationship with performance. In addition, this study aims to identify human resource development practice as a moderator in the relationship between service operations practices and the performance of local authorities. The research methodology employed is in the form of field study with the questionnaire as its instrument. The data is analysed using Pearson correlation and multiple regression methods. A total of 300 questionnaires were sent to departments in the local authority organisation, comprising town councils and municipal councils, with a response rate of 208 questionnaires (69.33%). By using factor analysis and descriptive statistics methods, the study found that the service operations practices of local authorities can be measured by the following seven dimensions–leadership practice, push-pull oriented in service operations, organisational culture, range of services provided, development and design of new services, human resource specialisation in service operations, and utilisation of information technology. For each dimension, the departmental heads of local authorities stated that their departments adopted a conducive organisational culture, push orientation in service operations, a high service introductory level, a high level of human resource specialisation, provide a wide range of services and use information technology to reduce operational cost. The findings showed that there are significant relationships between several dimensions of the service operations practices and the performance of local authorities. Furthermore, the variables of human resource development moderator (formal training, informal coaching and empowerment) also act to affect the relationship between service operations practices and the performance of local authorities. Finally, a post-hoc test was also conducted to identify the form of moderator in this study. The findings of this study can contribute to the development of theories and knowledge in this field as several dimensions of service operations practices have been identified as significant in influencing the performance of local authorities.